2007
DOI: 10.1185/030079908x253410
|View full text |Cite
|
Sign up to set email alerts
|

Utility of health states in chronic kidney disease: a structured review of the literature

Abstract: Many studies have estimated utilities in ESRD patients, but only a few have estimated utilities based upon public preferences. Further empirical research is needed to produce more reliable utilities for economic modelling in the UK, especially in chronic kidney disease patients who do not require dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…Finally, Dale and colleagues 77 reviewed studies of health utility in people with CKD and ESRD. Only one study 78 included this review met our inclusion criteria and was thus data extracted separately.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Dale and colleagues 77 reviewed studies of health utility in people with CKD and ESRD. Only one study 78 included this review met our inclusion criteria and was thus data extracted separately.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…These probabilities were estimated by removing deaths due to CVD and renal disease from the data used to derive the interim life-tables published by the UK Office for National Statistics. 204,205 Utilities A recent review of the literature 77 identified only one study reporting utility values (based on community preferences) for the full range of CKD states (stages 1 and 2 through to ESRD pre and post dialysis). This US study used HUI-3 to assign utility scores to 269 patients spread across the CKD stages.…”
Section: Mortality From Other Causementioning
confidence: 99%
“…Several studies have assessed the quality of life (QoL) of ESRD patients, invariably showing a considerably lower QoL in ESRD patients compared with CKD patients [3]. Costs of ESRD treatment modalities are high, with a share of the national expenditures in European countries ranging from 0.7% in the UK to 1.8% in Belgium (1.5% in France, 1.6% in Italy) [4].…”
Section: Introductionmentioning
confidence: 99%
“…We assumed that the cost of spontaneously resolving AR would be £145 (the cost of a clinic visit) and that the cost of steroid-sensitive AR could be approximated by HRG4 currency LA07P (acute kidney injury without treatment complication and comorbidity score 0-3), 48 as the cost of high-dose CCSs is not significant (in 2014/15 prices, this is £1274).…”
Section: Acute Rejectionmentioning
confidence: 99%
“…20,[43][44][45] Unfortunately, data relating specifically to quality of life are currently available only in the adult population, among whom there are clear quality-of-life improvements from having a functioning kidney transplant compared with being on dialysis. [46][47][48][49][50][51][52] Significance for the NHS Treatment for ESRD is considered resource-intensive for the NHS because current costs have been estimated to use 1-2% of the total NHS budget to treat 0.05% of the population (both adult and child/adolescent). 53 Based on data from the Department of Health, it is estimated that in 2008/9, the total expenditure on 'renal problems' in England was £1.3B, representing 1.4% of the NHS expenditure.…”
Section: Significance For Patientsmentioning
confidence: 99%